Surface modification of pH-responsive poly(2-(tert-butylamino)ethyl methacrylate) brushes grafted on mesoporous silica nanoparticles. Issue 1 (1st January 2019) - Alswieleh, Abdullah M.; Alshahrani, Mufleh M.; Alzahrani, Khalid E.; Alghamdi, Hamdan S.; Niazy, Abdurahman A; Alsilme, Abdulilah S; Beagan, Abeer M.; Alsheheri, Bayan M.; Alghamdi, Abdulaziz A.; Almeataq, Mohammed S.
ABSTRACT: Poly(2‑(tert-butylamino)ethyl methacrylate) brushes (PTBAEMA) are grown from mesoporous silica nanoparticles via surface-initiated atom transfer radical polymerization (SI-ATRP). Linear PTBAEMA brushes are protonated and highly swollen at low pH; brushes are collapsed at pH higher than 7.7 due to deprotonation, as determined by dynamic light scattering (DLS). Quaternization of these brushes is conducted using 2-iodoethanol in alkali media. DLS measurement of nanoparticles shows that surface-confined quaternization occurs and produces pH-responsive brushes with a hydrophobic upper surface. Variation of the 2-iodoethanol reaction time enables the mean degree of surface quaternization. The pH-responsive behaviour of quaternized PTBEAMA brushes at 1 h reaction time indicates low degrees of surface quaternization, dictated by the spatial location of 2-iodoethanol. Almost uniformly quaternized brushes prepared when the conducted for 3 h and became less swollen at low pH than brushes that conducted for 1 h. The intensity of the C − C − O component (286.5 eV) in the C1s X-ray photoelectron spectrum increased, suggesting that the reaction with iodoethanol was successful occurred.